Evaluation of the complete Sniffin Sticks Test versus its subtests in differentiating Parkinson's disease patients from healthy controls - Trentin, Sheila; Oliveira, Bruno Samuel Fraiman de; Borges, Yuri Ferreira Felloni; Rieder, Carlos Roberto de Mello (Arquivos de Neuro-Psiquiatria, 2022)
Background Hyposmia is one of the most common, as well as the first nonmotor condition in Parkinson disease (PD). The sniffin sticks test (SST) evaluates three different aspects of olfactory function: threshold (T), discrimination (D), and identification (I). The sum of the scores of these three subtests produce a global score of olfaction, the Threshold-Discrimination-Identification (TDI) score.Objective The aim of this study was to investigate if the TDI score or one of its subtests is better to discriminate PD patients from controls.Methods We recruited 27 PD patients and 17 healthy age-matched controls (HC) who were evaluated through a clinical interview, the Montreal Cognitive Assessment and Movement Disorders Society – Unified Parkinson Disease Rating Scale. The olfaction was assessed using the complete SST.Results The performance of PD patients on the olfactory test was significantly worse when compared with the HC (T: 3.0 vs. 6.5, p < 0.001; D: 8.1 vs. 11.2, p < 0.001; I: 7.3 vs. 11.7, p < 0.001; TDI: 18.8 vs. 29.9, p < 0.001). The prevalence of olfaction impairment in our study (PD: 100%, and HC: 56%) was greater than that found in the literature. Cognition influenced the performance on TDI. The olfactory subtests were impaired proportionally between patients and controls. Furthermore, D and I were correlated, but only in PD patients. The TDI showed a tendency to better discriminate PD patients from HC, when compared with its subtests.Conclusions Although the complete olfactory evaluation is time consuming, it seems to be a superior tool to identify olfaction impairment in PD patients, when compared with the isolated subtests.
Keywords: Parkinson Disease; Anosmia; Smell